The predictive role of maternal serum and cervicovaginal fluid vitamin D-binding protein for preterm birth and latency period - Ozen, Ayten Nesibe; Ozgen, Gulten; Dincgez, Burcu; Ozgen, Levent (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
Adverse perinatal outcomes have been linked to alterations in vitamin D-binding protein (VDBP) levels. We assessed the predictive value of serum and cervicovaginal fluid VDBP for preterm birth, as well as to measure VDBP in threatened preterm labor (TPL) and preterm premature rupture of membranes (PPROM).A total of 138 pregnant women were divided into three groups in this prospective case-control study: TPL(n=59), PPROM (n=43) and control (n=36). Also, all patients were divided into two groups according to whether the latency period was shorter (n=48) or longer than 48 hours (n=90). The VDBP levels were measured using an enzyme-linked immunosorbent assay kit and compared between groups.Cervicovaginal fluid and serum VDBP levels were lower in the TPL and PPROM groups than controls. Cervicovaginal fluid VDBP<0.63ng/ml predicted preterm birth with 81.58% sensitivity and 53.23% specificity (AUC=0.713, p<0.001). Serum VDBP≤ 0.26ng/ml predicted preterm birth with 61.84% sensitivity and 64.52% specificity (AUC=0.629, p=0.008). No significant difference was detected between serum and cervicovaginal fluid VDBP levels for predicting preterm birth (p=0.018). Moreover, cervicovaginal fluid VDBP>0.44ng/ml predicted latency period≤48 hours with 43.75% sensitivity and 94.44% specificity (AUC=0.694, p<0.001), while serum VDBP did not predict a latency period shorter than 48 hours (AUC=0.515, p=0.771).Both serum and cervicovaginal VDBP may be valuable markers for predicting preterm birth. Although no difference was found between serum and cervicovaginal VDBP in terms of predictive role, cervicovaginal fluid VDBP may be one step ahead of serum VDBP with the ability to predict a short latency period
Keywords: cervicovaginal vitamin D-binding protein; latency period; preterm birth; serum vitamin D-binding protein